REFERENCE MATERIALS INSTITUTE DEVELOPER AND PRODUCER OF REFERENCE MATERIALS OF RAW AND METALLURGICAL PRODUCTION MATERIALS - V. V. Stepanovskikh (Стандартные образцы)
The article describes the history of creation of Russian reference materials (RMs), the stages of start-up and development of the Institute for Certified Reference Materials as a main producer of RMs of metallurgical production in Russia. The article considers the experience of the Institute for Certified Reference Materials for RMs development and metrological assurance of quantity chemical analysis based on their use.